Pelatihan dan Kompetisi Mama Volleyball bagi Ibu-ibu Se Daerah Istimewa Yogyakarta - Sujarwo; Edi Purnomo; Fitria Dwi Andriani; Nursita Utami (JURNAL PENGABDIAN MASYARAKAT OLAHRAGA DAN KESEHATAN (JASO), 2026)
This training aims to provide education and also an opportunity to show off the volleyball skills of mothers in the Special Region of Yogyakarta who participated in this activity. The training activity method is with the presentation of material from the lecturer to the participants, the second method is with competitions between participating teams. Participants in this community service activity are mothers who are members of four teams with a total number of participants: 21 people. The results of the community service implementation showed an increase in knowledge about volleyball mama by 0.89% seen from the average test results before and after the training. The conclusion of community service about volleyball mama is very much needed by the participants to socialize and also update knowledge about volleyball material and the effect is expected to be their sons and daughters become interested in playing volleyball.